Assessing treatment effects in older breast cancer patients: Systematic review of observational research methods. Issue 3 (March 2015) - de Glas, N.A.; Kiderlen, M.; de Craen, A.J.M.; Hamaker, M.E.; Portielje, J.E.A.; van de Velde, C.J.H.; Liefers, G.J.; Bastiaannet, E.
Highlights Observational research will be essential to improve treatment of older breast cancer patients. The use of accurate methods is essential to draw valid conclusions from this type of data. The majority of observational studies in older breast cancer patients compared treatments directly. These studies are therefore likely to be biased due to confounding by indication.